MULTIPARAMETRIC FLOW CYTOMETRY REFINES RISK STRATIFICATION IN NEWLY DIAGNOSED MULTIPLE MYELOMA PATIENTS - Fazio, Francesca; Lapietra, Gianfranco; Limongi, Maria Zaira; Intoppa, Stefania; Milani, Maria Laura; Piciocchi, Alfonso; Martelli, Maurizio; Guarini, Anna; Foà, Robin; De Propris, Maria Stefania; Petrucci, Maria Teresa (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Multiple myeloma (MM) is a heterogeneous malignancy characterized by the proliferation of abnormal plasma cells in the bone marrow. Multiparametric flow cytometry (MFC) plays a role in the work-up of the disease in view of the aberrant expression of surface antigens. Our study aimed at describing the antigenic profile detected by MFC in a series of newly diagnosed MM patients to correlate the level of expression with other features of the disease. Between April 2018 and June 2022, 84 consecutive MM patients were studied at presentation. CD56 and CD117 were commonly detected, while CD45, CD28, CD20, CD19, CD13 and CD33 were less recurrent. CD20 expression was associated with the type of secretory MM (p=0.041) and with a higher disease burden (p=0.038). CD28 positivity correlated with a lower platelet count at baseline (p=0.005) and with a lower rate of complete response (p=0.038). Furthermore, CD28 positivity and a lower CD138 expression tended to associate with the high-risk chromosomal translocations t(14;16) and t(4;14). The results of this study indicate that in the diagnostic work-up of MM, MFC may help to identify different patient subsets and improve risk stratification. These observations need to be validated in larger series of patients with a longer follow-up.